Stumbling Through the Dark - Rüber,Till (2025)
This project aims to study wide angle scattering events at LDMX through simulation. LDMX is a fixed target experiment searching for missing momentum of the beam electrons to identify dark matter signals. It consists of a tracking system around the thin tungsten target placed in a 1.5 T magnetic field, to measure the momentum of electrons before and after the target, and calorimeters (electromagnetic and hadronic) to obtain the energy of the electrons. In wide angle scattering events, the beam electron undergoes hard scattering in the target and misses the ECal so that it only produces a track in the recoil tracker and a signal in the side HCal. It is important to correctly identify this type of event to distinguish them from possible DM signals. The project work includes the development of a configurable generator to produce wide angle scattering events, as well as the modification and expansion of the existing reconstruction method for the side HCal, which uncovered an existing issue that could be resolved. Furthermore, an energy weighting of reconstructed hits remains to be implemented to account for energy deposition in the absorber material. The particle flow algorithm, matching signals in different detector components, is extended such that a track can be matched to an HCal cluster and a sample of 10,000 events is analysed. This analysis confirms the successful development of the generation, reconstruction and particle flow algorithms. It also reveals that the clustering algorithm needs to be optimised and a satellite clustering algorithm should be implemented to correctly identify wide angle scattering events. The configuration parameters of these two algorithms need to be adjusted to ensure their reliable performance on events with simultaneous electron signals (pileup events).
Keywords: LDMX; wide angle scattering event; dark matter; bachelor degree project; report